Structural and Functional NIR-II Fluorescence Bioimaging in Urinary System via Clinically Approved Dye Methylene Blue - Dingwei Xue; Di Wu; Zeyi Lu; Jochen Neuhaus; Abudureheman Zebibula; Zhe Feng; Sheng Cheng; Jing Zhou; Jun Qian; Gonghui Li (Engineering, 2023)
Accurate structural and functional imaging is vital for the diagnosis and prognosis of urinary system diseases. Fluorescence bioimaging in the second near-infrared spectral region (NIR-II, 1000–1700 nm) has shown advantages of higher spatial resolution, deeper penetration, and finer signal-to-background ratio (SBR) compared to the conventional fluorescence imaging methods but limited to its clinical inapplicability. Herein, we first report in vivo NIR-II fluorescence imaging of the urinary system enabled by a clinically approved and renal excretable dye methylene blue (MB), which cannot only achieve clear invasive/non-invasive urography but also noninvasively detect renal function efficiently. These results demonstrate that MB assisted NIR-II fluorescence imaging holds a great promise for structural and functional imaging of the urinary system both clinically and preclinically.